2015
DOI: 10.1177/0284185114538792
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment staging of multiple myeloma patients: comparison of whole-body diffusion weighted imaging with whole-body T1-weighted contrast-enhanced imaging

Abstract: Background: Multiple myeloma (MM) is a hematologic malignancy characterized by the clonal proliferation of plasma cells. Accurate staging is of pivotal importance in the management of MM. Advanced imaging techniques, such as magnetic resonance imaging (MRI), are increasingly used for the initial diagnosis and staging of MM. Purpose: To compare whole-body (WB) MR diffusion-weighted imaging with background body signal suppression (DWIBS) with (WB) MR fat-suppressed T1-weighted contrast-enhanced imaging (T1-CE) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In recent years, new imaging techniques, such as PET or MRI, play an increasingly important role in staging of MM. The impact of MRI on staging patients according to DS Plus has been analyzed in many studies [ 12 14 ]. Although 18 F-FDG PET/CT has been proved to be prognostically valuable in staging different groups [ 15 17 ], only few studies have been reported on DS Plus based on 18 F-FDG PET/CT [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, new imaging techniques, such as PET or MRI, play an increasingly important role in staging of MM. The impact of MRI on staging patients according to DS Plus has been analyzed in many studies [ 12 14 ]. Although 18 F-FDG PET/CT has been proved to be prognostically valuable in staging different groups [ 15 17 ], only few studies have been reported on DS Plus based on 18 F-FDG PET/CT [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly MRI depicts marrow infiltration and replacement, while radiographs and CT illustrate osseous destruction, and because of this MRI has superior detection of bone marrow involvement compared with LDWBCT or PET/CT, with a specific advantage in the diffuse patterns of involvement . Incorporation of DWI results in superior lesion conspicuity compared with conventional STIR and contrast‐enhanced MRI, and ADC values can be used with excellent accuracy (90% sensitivity and 93% specificity) to differentiate diseased and normal marrow . Quantitative ADC analysis has shown particular value in determining diffuse involvement; a bone marrow ADC greater than 0.548 × 10 −3 mm 2 /s has been shown to be 100% sensitive and 98% specific for diagnosing a diffuse marrow pattern …”
Section: Applications Of Pet‐mri In Oncologic Musculoskeletal Diseasementioning
confidence: 99%
“…It is not necessary for bone evaluation in the vast majority of patients (46). Several authors have used gadolinium-based contrast agent injection in a global approach to disease staging in MM and lymphoma (47), but this may not be necessary if whole-body DWI is performed (48).…”
Section: Whole-body Mr Imaging Protocols In Oncologymentioning
confidence: 99%